New application for the identification and differentiation of microplastics based on fluorescence lifetime imaging microscopy (FLIM). Issue 1 (February 2021) - Monteleone, Adrian; Wenzel, Folker; Langhals, Heinz; Dietrich, Daniel
Graphical abstract: Cryo-milling of various plastic types into microplastic particles and detection via FLIM Highlights: FLIM measures fluorescence lifetime of plastics and thus can be used for identification and characterization of plastics FLIM offers additional morphological information as well as information about the size and surface of plastics Heat treatment causes changes in photon count and stable variations in fluorescence lifetime Abstract: The problem of micro- and nanoplastic (short: plastics) pollution is an increasing global issue and therefore several detection methods for plastics, also investigating the chemical nature via spectroscopy and chromatography, have been developed over the years. A new approach for identification and characterization of plastics is fluorescence lifetime imaging microscopy (FLIM) – a microspectroscopic method to detect fluorescence lifetime ( τ ) of plastics. We tested whether FLIM can be employed for the identification and characterization of plastics. Six types of plastics (ABS, PA6, PET, PLA, PPE, PU), with and without prior heat treatment, were subjected to FLIM with excitation wavelengths of 470 nm and 440 nm. The results provided mean τ (intensity weighted) values of 3.850 (+- 0.033) ns for ABS, 8.143 (+- 0.060) ns for PPE, 3.519 (+-0.090) ns for PET of a bottle from Germany and 3.564 (+-0.126) ns for PET of a bottle from the USA. The combination of mean intensity weighted τ and mean amplitude weighted τ values allowed for the significant differentiation of 52 (94.55 %) of the 55 possible plastic comparisons. Moreover, FLIM showed the potential for the sub-micrometer range plastic characterization, phasor analysis and allows for visual 3D-sectioning of samples that could be important for identification and characterization of plastics in tissue and environmental samples.